Silencing the Subaltern: Postcolonial Literary Voices & Contemporary Military Power in Indonesia - Zukhrufa Meyvicka (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This article examines the increasing influence of military power in Indonesian politics, the 2025 revision of the National Armed Forces (TNI) Law, and the growing restrictions on press freedom. Anchored in postcolonial theory—specifically Gayatri Spivak’s concept of the subaltern and Edward Said’s Orientalism—this study explores how state and military institutions silence public voices, particularly in the context of the recent legislation and the nationwide protests of March 20–28, 2025. Using a qualitative descriptive approach, with close reading as the primary research instrument, the analysis focuses on the character of Okonkwo and selected narrative elements in Chinua Achebe’s Things Fall Apart. The article compares silencing in the novel with current repressive actions in Indonesia to argue that colonial legacies endure not only in social and political structures but also in strategies of power consolidation. The findings suggest that literary representations of colonial domination mirror broader patterns of militaristic control in postcolonial states. This study identifies structural parallels between the silencing of subaltern characters in the novel and ongoing restrictions on civil and media freedoms in Indonesia. Postcolonial literature, therefore, is not only a historical reflection but a critical lens through which to understand modern state power and its enduring colonial imprints.